2022
DOI: 10.1111/cyt.13175
|View full text |Cite
|
Sign up to set email alerts
|

Cell block‐based RNA next generation sequencing for detection of gene fusions in lung adenocarcinoma: An institutional experience

Abstract: Objective: Targeted therapy is an important part of the treatment of lung adenocarcinoma. Tests for EGFR mutation, ALK, ROS1, RET and NTRK gene fusions are needed to make a treatment decision. These gene fusions are traditionally detected by fluorescence in situ hybridisation (FISH) or immunohistochemistry. In this study, we investigated whether gene fusions in pulmonary adenocarcinoma could be accurately detected by RNA next-generation sequencing (RNA-NGS) and whether cytology cell blocks could be used effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…cg07936950, cg05938001, cg12308746, and cg17737681 were the four CpG sites with the highest DNA methylation. Targeted therapy is also an important component of lung cancer treatment, and treatment regimens require testing for EGFR, ALK, ROS1, RET, MET, BRAF, NTRK, HER2, NRG1, FGFR1, and PIK3CA ( Guo et al, 2019 ; Wei et al, 2023 ). When further testing the sensitivity of DLX1 gene mutations in LUAD, we found that the incidence of DLX1 gene mutations in LUAD tissues was only 1.5% by cBioPortal study.…”
Section: Discussionmentioning
confidence: 99%
“…cg07936950, cg05938001, cg12308746, and cg17737681 were the four CpG sites with the highest DNA methylation. Targeted therapy is also an important component of lung cancer treatment, and treatment regimens require testing for EGFR, ALK, ROS1, RET, MET, BRAF, NTRK, HER2, NRG1, FGFR1, and PIK3CA ( Guo et al, 2019 ; Wei et al, 2023 ). When further testing the sensitivity of DLX1 gene mutations in LUAD, we found that the incidence of DLX1 gene mutations in LUAD tissues was only 1.5% by cBioPortal study.…”
Section: Discussionmentioning
confidence: 99%
“…7 Much of the literature regarding next generation sequencing has involved analysis of larger specimen types including core needle biopsies and resection specimens but cytology has been demonstrated to be a useful alternative when larger specimens are unavailable. [8][9][10][11][12][13][14] NGS testing of cytology specimens has been shown to be useful for analysis of malignancies from a variety of body sites including the lung, salivary gland, pancreas, and thyroid. 8,10,11,14 Cytologic specimens suitable for NGS testing include cell blocks, 11,12 smeared specimens, cytospins and liquid based preparations.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13][14] NGS testing of cytology specimens has been shown to be useful for analysis of malignancies from a variety of body sites including the lung, salivary gland, pancreas, and thyroid. 8,10,11,14 Cytologic specimens suitable for NGS testing include cell blocks, 11,12 smeared specimens, cytospins and liquid based preparations. 8,9 When properly performed, NGS testing of cytology specimens appears to be as accurate as testing of larger surgical specimens.…”
mentioning
confidence: 99%